Gender and Economic Sanctions: An Analysis of the Gendered Consequences of Economic Sanctions and Gender Empowerment Programs - Murdoch-Fyke, Airianna (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2022)
Economic sanctions will likely remain the preferred method of peaceful coercion. Therefore, the resulting gendered consequences must be addressed and mitigated within the existing framework of sanctions. Unfortunately, civilians cannot be completely protected from the consequences of sanctions. However, the gender specific effects of economic sanction can be minimized to protect women from suffering disproportionate harms. To abate gendered consequences, the international community, when imposing a sanction regime, must simultaneously permit and fund the implementation of gender empowerment programs (GEP) in the targeted state. While GEP would not protect women from all the effects of sanctions, GEP would provide programming to minimize the consequences sanctions have on female economic independence and women’s health.  First, GEP would assist women gain, or regain, economic independence through access to education and formal labor markets, improving their overall economic wellbeing and ability to withstand economic shocks created by sanctions. Second, GEP would provide programs to improve women’s access to health and water, sanitation and hygiene (WASH), as well as improved food security, and support services to reduce the prevalence of, and/or minimize the effects of, sexual and gender-based violence (SGBV). GEP would help reduce the long-term and cyclical gendered consequences of sanctions and reduce the financial dependency many women, especially female-headed households, have on government support programs and exploitative informal income. This article is presented in three parts. The first part of examines the consequences of economic sanctions and discusses the humanitarian exemption approval process. Next, this article outlines gender empowerment programming, focusing on two components of female economic independence and the impact economic sanctions, humanitarian exemptions, and GEP have on this independence. Finally, this article focuses on the impact economic sanctions, humanitarian exemptions, and GEP have on women’s health, including access to healthcare, SGBV, food and nutrition, and appropriate water, sanitation, and hygiene.